(6x^2 + 11xy - 11y^2) + (3x^2 - 5xy - 8y^2)

= x^2(6+3) + xy(11-5) + y^2(-11-8)

= x^2(6+3) + xy(11-5) + y^2(-11-8)

**= 9x^2 + 6xy - 19y^2**(6x^2 + 11xy - 11y^2) + (3x^2 - 5xy - 8y^2)

= x^2(6+3) + xy(11-5) + y^2(-11-8)

** = 9x^2 + 6xy - 19y^2**

= x^2(6+3) + xy(11-5) + y^2(-11-8)

(6x^2 + 11xy - 11y^2) + (3x^2 - 5xy - 8y^2)

= (6x^2 + 3x^2) + (11xy - 5xy) + (-11y^2 - 8y^2)

= 9x^2 + 6xy - 19y^2

= (6x^2 + 3x^2) + (11xy - 5xy) + (-11y^2 - 8y^2)

= 9x^2 + 6xy - 19y^2

The question is

(6x^{2}+11xy- 11y^{2}) - (3x^{2} - 5xy - 8y^{2})

expanding

6x^{2}+11xy - 11y^{2}-3x^{2}+5xy+8y^{2}

adding like terms

6x^{2}+16xy- 11y^{2}-3x^{2}+8y^{2}

subtracting like terms:

3x^{2}+16xy-3y^{2}

(6x

expanding

6x

adding like terms

6x

subtracting like terms:

3x

Didn't find the answer you were looking for?